1990
DOI: 10.1055/s-0038-1647353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of International Normalized Ratios by a Controlled Field Survey with 4 Different Thromboplastin Reagents

Abstract: SummaryA nationwide survey has been performed in Japan involving 75 laboratories to assess the relative reliability of different methods of reporting prothrombin time results in anticoagulant control. The interchangeability of results using prothrombin time, prothrombin activity percentage, prothrombin ratio and international normalized ratios (INR) were compared with four different thromboplastin reagents and a range of coagulometers. A secondary batch of reference thromboplastin of human brain origin (BCT/45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…Others 16,36/38 have reported that despite this deviation, lyophilized plasmas can be used to calculate the INR and to calibrate thromboplastins. Clearly, our study shows that calibration is more reliable with AK Cal plasmas than with ART Cal plasmas, 31 as also recently reported by Stevenson et al 39 However, AK Cal plasmas are limited in supply, costlier, and subject to ethical and regulatory issues and to possible batch-tobatch variability. Second, it is not easy to provide the wide range of INR values required for accurate ISI calibration on pooled AK Cal plasmas.…”
Section: Inr Standardization Using Plasma Calibrantssupporting
confidence: 64%
See 1 more Smart Citation
“…Others 16,36/38 have reported that despite this deviation, lyophilized plasmas can be used to calculate the INR and to calibrate thromboplastins. Clearly, our study shows that calibration is more reliable with AK Cal plasmas than with ART Cal plasmas, 31 as also recently reported by Stevenson et al 39 However, AK Cal plasmas are limited in supply, costlier, and subject to ethical and regulatory issues and to possible batch-tobatch variability. Second, it is not easy to provide the wide range of INR values required for accurate ISI calibration on pooled AK Cal plasmas.…”
Section: Inr Standardization Using Plasma Calibrantssupporting
confidence: 64%
“…Moreover, the manufacturer's stated ISI of the thromboplastin is derived from World Health Organization recommendations and applies only to manual techniques, whereas automation is rapidly increasing and diversifying. 8 31 have suggested that manufacturers give the ISI of the thromboplastin-instrurnent system, and some express the ISI according to the type of clot-detecting system (optical or mechanical). Poggio et al 16 showed that the calibration of some commercial reagents tested on coagulometers against the reference material (manual testing) raises further problems in slope determination.…”
Section: Discussionmentioning
confidence: 99%
“…106 Several investigators have noted incorrect ISI values provided by manufacturers of thromboplastin reagents. [107][108][109] Although local calibrations can be performed with plasma samples with certified PT values to determine the instrument-specific ISI, the process is tedious and beyond the scope of many laboratories.…”
Section: Monitoring Oral Anticoagulant Therapymentioning
confidence: 99%
“…98 -103 In general, the College of American Pathologists has recommended that laboratories use responsive thromboplastin reagents (ISI Ͻ1.7) and reagent/instrument combinations for which the ISI has been established. 104 ISI values provided by manufacturers of thromboplastin reagents are not invariably correct, [105][106][107] and this adversely affects the reliability of measurements. Local calibrations can be performed by using plasma samples with certified PT values to determine the instrument-specific ISI.…”
Section: Monitoring Anticoagulation Intensitymentioning
confidence: 99%